The effect of organizational commitment on safety behaviors: Moderating effects of safety climate - Moon, Kwangsu; Lee , Jaehee; Oah, Shezeen (Korean Journal of Industrial and Organizational Psychology, 2011)
The purpose of this study was to examine the effects of organizational commitment on safety behavior and to explore moderating effect of safety climate between organizational commitment and safety behaviors. 215 workers were asked to respond to the questionnaires that measured various demographic variables, organizational commitment, safety climate and safety behaviors. A hierarchical regression was conducted to identify variables that had significant relationships with safety behaviors and to examine moderating effect of safety climate between organizational commitment and safety behaviors. Results indicated that the emotional commitment significantly predicted both safety compliance and participation behavior and the normative commitment significantly predicted safety compliance behavior. It was found that the safety climate was also a significant predictor for both safety compliance and participation behavior. In addition, safety climate had a moderating effect on the relation between emotional commitment and safety compliance behavior and normative commitment and safety compliance and participation behavior. Based on these results, the implications of this study and suggestions for future research were discussed.